GENDER DALAM PERSPEKTIF AL-QUR’AN - Djamaluddin, Ahdar (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2015)
This paper attempts to understand and analyze issues of gender relations between men and women according to the Qur?an with the two sub-points. First, how is gender identity used in the Qur'an. Second, how does the Qur?an speaks of gender equality? The position of women from history has influenced the understanding of most Islamic scholars. Even some of what is considered religion, in fact it is derived from culture and those views. This precisely caused the difference opinion about partnership of men and women. Understanding religious texts even any text is influenced by many factors. It is not only knowledge but also the level of educational background, culture and social condition of society. Meanwhile, it is also misunderstanding the text and the background to understand the nature of language.